A new species of Isonychia Eaton, 1871 (Ephemeroptera: Isonychiidae) from Kapila River, Central Western Ghats, India - Muthukatturaja, M.; Balasubramanian, C.; Rathinakumar, T.; Sivaramakrishnan, K. G. (Zootaxa, 2021)
Isonychia (Isonychia) radhae n. sp. is described based on larvae and imagoes from Kapila River, Dakshina Kannada, Karnataka State, India. The imagoes of I. radhae n. sp. can be distinguished from the other known Oriental species by the following combination of characters: (i) absence of rusty brown maculae in the costal, subcostal, and median areas of forewing; (ii) forelegs dark brown except coxae; (iii) Scattered barbs present in penis; (iv) Second segment of gonostylus long and slender; and (v) sterna of abdominal segment X in female not deeply cleft. Isonychia radhae n. sp. can be distinguished in the larval stage from other known Oriental species by the following combination of characters: (i) tergites II–IV without distinct stripe medially, tergites V–X with a pair vague oblique stripe; (ii) abdominal terga II–IX with median dark brown maculae progressively larger with dark brown slanting streaks in lateral margins; (iii) gills I and II small, tracheae of abdominal gills I–VII unbranched; (iv) postero-lateral projection on anterior segments of abdomen blunt and small, acute on segments VIII–IX and large at on segment IX; (v) median terminal filament slightly shorter than 1/3 length of cerci; (vi) distal segments of cerci dark, basal ¾ of mesal margin of cerci and lateral margin of terminal filament with long thin setae. Revised keys to the known larvae and male imagoes of Oriental species of Isonychia are also provided.